2017
DOI: 10.1038/npp.2017.39
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Choline-Containing Compound Levels in Rapid Cycling Bipolar Disorder

Abstract: Previous studies have found increased levels of choline-containing compounds (ie, glycerophosphocholine plus phosphocholine (GPC+PC)) in bipolar disorder using in vivo proton magnetic resonance spectroscopy (H MRS), especially in bipolar I disorder (BD-I). Increased levels of GPC+PC suggest alterations in the membrane phospholipids metabolism in bipolar disorder. Rapid cycling (RC) bipolar disorder is considered as a severe course of bipolar disorder, but it is unclear whether rapid cycling bipolar disorder is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 58 publications
(62 reference statements)
0
4
0
1
Order By: Relevance
“…For example, arachadonic and docosahexaenoic acid were found to be reduced in red blood cell membranes of BD patients in a manic phase [ 22 ]. Another study used in vivo proton magnetic resonance spectroscopy and found increased glycerophosphocholine plus phosphocholine levels in the basal ganglia and anterior cingulate cortex of patients with BD, which are brain regions that are important for mood regulation [ 23 ]. Moreover, Knowles et al recruited a sample of 558 individuals from 38 extended pedigrees and analyzed 13 serum-based phospholipid concentrations; they concluded that serum-based phosphatidylinositol had a significant association with BD risk [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, arachadonic and docosahexaenoic acid were found to be reduced in red blood cell membranes of BD patients in a manic phase [ 22 ]. Another study used in vivo proton magnetic resonance spectroscopy and found increased glycerophosphocholine plus phosphocholine levels in the basal ganglia and anterior cingulate cortex of patients with BD, which are brain regions that are important for mood regulation [ 23 ]. Moreover, Knowles et al recruited a sample of 558 individuals from 38 extended pedigrees and analyzed 13 serum-based phospholipid concentrations; they concluded that serum-based phosphatidylinositol had a significant association with BD risk [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies that investigated clinical groups and included a healthy control group were included in the clinical population analysis. There were 180 publications [141,142,157,305,306,308,310312,317,321,322,328,160,329333,335,337,339341,161,342,345,350354,359361,162,362,364,365,368374,163,377,378,380387,165,388397,166,398407,167,408414,169,171,143,174,175,178,179,181,183185,187,188,144,190,192,193,195201,145,203,204,207211,213215,146,217,219,220,223,227,229231,233,235,150,237,238,240,243,247,249,250,253,254,256,151,…”
Section: Methodsmentioning
confidence: 99%
“…First, they mark a point in favor of the pathophysiological process mentioned above; indeed, each molecule analyzed in these studies has a pathophysiological correlation with BD. As mentioned before, there is a process of neuronal damage in BD; thus, molecules such as n-acetyl-aspartate (NAA) and choline (Cho) translate a neurodegenerative process [ 21 ] and impaired repair of neuronal membranes, respectively [ 22 ]. Consequently, in BD there is a decrease in NAA, reflecting a loss of neuronal integrity [ 23 ], and an increase in Cho, which translates into cell membrane damage and altered metabolism of neuronal membranes [ 24 ].…”
Section: Reviewmentioning
confidence: 99%